Electrochemical study of arsenopyrite weathering - Almeida, CMVB; Giannetti, B. F. (Royal Soc Chemistry, 2003)
Cyclic voltammograms and capacitance measurements are presented to characterize the mineral response at relatively moderate environmental conditions, pH 4.5 and T = 25degreesC. The experiments involve examining the rates of oxidation and the surface morphology of arsenopyrite, which is oxidized abiotically. The semiconducting properties of the mineral have been investigated in attempt to gain additional information of FeAsS dissolution behavior in acidic solutions at potentials close to the open circuit potential of the mineral. A mechanistic pathway for the anodic dissolution of arsenopyrite in open circuit conditions is also suggested. At high overpotentials, anodic reactions produce mainly sulfate and arsenate ions and may be described as hole limited. The reduction of orpiment-like compounds at potentials more negative than the open circuit potential is discussed.